Are Enterocolic Mucosal Mast Cell Aggregates Clinically Relevant in Patients Without Suspected or Established Systemic Mastocytosis?. (October 2018) - Johncilla, Melanie; Jessurun, Jose; Brown, Ian; Hornick, Jason L.; Bellizzi, Andrew M.; Shia, Jinru; Yantiss, Rhonda K.
Abstract : The World Health Organization considers enterocolic mast cell aggregates with atypical morphologic and/or immunohistochemical features diagnostic of systemic mastocytosis mostly because published data are heavily influenced by inclusion of symptomatic patients with systemic disease. We occasionally encounter atypical mast cells in gastrointestinal biopsy samples from patients in whom systemic mastocytosis is not suspected. The aim of this study was to describe the clinicopathologic features and implications of atypical enterocolic mast cell aggregates in 16 patients without suspected or established systemic mastocytosis. Mast cell infiltrates were assessed for morphology, distribution, associated inflammatory cells, and CD117 and CD25 immunoexpression. Most (63%) patients were women; 15 underwent endoscopic examination for screening (n=7), abdominal pain (n=3), diarrhea (n=3), changing bowel habits (n=1), and dysphagia (n=1). Mast cell aggregates were detected in 1 colectomy specimen for cancer. Colonic involvement was most common (n=14) and resulted in polypoid (n=10), edematous (n=2), or normal (n=3) mucosae. All cases featured CD117/CD25 +, ovoid mast cells concentrated beneath the epithelium, or diffusely involving the entire mucosal thickness. Eosinophils were numerous and obscured mast cells in 63% of cases. Spontaneous resolution of symptoms occurred in all patients (mean follow-up: 54 mo), and asymptomatic patients remained symptom-free (mean follow-up: 17 mo). Of 4 patients evaluated for systemic mastocytosis, 3 had negative bone marrow biopsies and one lacked a KIT mutation in peripheral blood. We conclude that, although careful clinical assessment of patients with incidental enterocolic mast cell aggregates is reasonable, labeling them with a systemic hematologic disorder may not be justified.